Stimulation of Proliferation and Migration of Mouse Macrophages by Type B CpG-ODNs Is F-Spondin and IL-1Ra Dependent - Chen, Tai-An; Liao, Chiao-Chun; Cheng, Yung-Chih; Chen, Yen-Po; Hsu, Yi-Fan; Liang, Chi-Ming; Liang, Shu-Mei (PLOS ONE, 2015)
Macrophage proliferation and migration are important for many facets of immune response. Here we showed that stimulation of macrophages with type B CpG oligodeoxynucleotides (CpG-B ODNs) such as CpG-ODN 1668 increased the production of anti-inflammatory cytokine interleukin 1 receptor antagonist (IL-1Ra) in a TLR9- and MyD88-dependent manner. The CpG-B ODNs-induced IL-1Ra increased macrophage migration and promoted macrophage proliferation by down-regulating the expression of a cell cycle negative regulator, p27 to increase cell population in the S phase. The induction of IL-1Ra by CpG-B ODNs was F-spondin dependent. Knockdown of F-spondin and IL-1Ra decreased CpG-B ODNs-induced macrophage migration whereas overexpression of IL-1Ra increased migration of those cells. These findings demonstrated novel roles for F-spondin and IL-1Ra in CpG-B ODNs-mediated cell proliferation and migration of macrophages.